Natural Killer Cell Activity and Interleukin-12 in Metabolically Healthy versus Metabolically Unhealthy Overweight Individuals - Kim, Minjoo; Kim, Minkyung; Yoo, Hye Jin; Lee, Jong Ho (Frontiers in Immunology, 2017)
The purpose of this study was to determine whether the immune system is associated with the different metabolic environments in healthy and unhealthy overweight individuals. We examined the metabolic and immune characteristics of 117 overweight individuals. Subjects were classified as metabolically healthy overweight (MHO, n = 72) or metabolically unhealthy overweight (MUO, n = 45) based on definitions set by the National Cholesterol Education Program (NCEP) Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (Adult Treatment Panel III; ATP III). The immune response was measured by circulating levels of natural killer (NK) cell activity and cytokines. NK cell activity was evaluated based on the ratio of effector cells (E; peripheral blood mononuclear cells, PBMCs) to target cells (T; K-562 cells) at E:T ratios of 10:1, 5:1, 2.5:1, and 1.25:1. Both groups were comparable with regards to age, sex distribution, smoking status, drinking status, and body mass index (BMI). When compared with the MHO group, the MUO group showed higher systolic and diastolic blood pressure, serum levels of triglyceride, glucose, insulin, and homeostatic model assessment of insulin resistance (HOMA-IR) index and lower levels of HDL cholesterol. Compared to the MHO group, the MUO group showed 39% lower IFN-γ levels (not significant) and 41% lower IL-12 levels (significant). The MUO group also showed lower NK cell activity at E:T ratios of 10:1 (P = 0.013), 5:1 (P = 0.043), 2.5:1 (P = 0.040), and 1.25:1 (P = 0.012) than the MHO group. This study indicates that individuals displaying the MUO phenotype present an unfavorable immune system with lower NK cell activities under all assay conditions and lower serum levels of IL-12 than the activities and levels in similarly overweight MHO individuals. This result suggests that the immune system may be altered in overweight individuals who are at risk for overweight/obesity-related comorbidities.